The role of carbon monoxide in the regulation of neuroendocrine function. - Mancuso, C; Preziosi, P; Grossman, AB; Navarra, P (1997)
This paper discusses the current evidence supporting the notion that endogenous carbon monoxide (CO) is a modulator of neuroendocrine function. CO is normally formed in the body during the enzymatic catabolism of heme moieties by heme oxygenase (HO). Three HO isoforms have been described to date: HO-1, HO-2 and HO-3. In the brain, CO is principally generated by HO-2 but, in discrete brain areas such as the paraventricular nuclei of the hypothalamus, a role for HO-1 is also possible. Moreover, under pathological conditions, the latter isoform is expressed by activated glial cells. The possible contribution by the recently described HO-3 remains to be established. Once formed, CO exerts its biological effects mainly via the activation of soluble guanylyl cyclase, but alternative signaling mechanisms, such as the activation of cyclooxygenase or the inhibition of cytochrome P450, have also been reported. In in vitro studies, the formation of CO within the hypothalamus has been associated with inhibition of the release of hormones such as corticotropin-releasing hormone, arginine vasopressin and oxytocin involved in hypothalamo-pituitary-adrenal axis activation and, conversely, with stimulation of luteinising hormone-releasing hormone release, thus suggesting that the gas may have a neuroendocrine role which may be to prevent over-exuberant activation of the hypothalamo-pituitary-adrenal axis and inhibition of reproductive processes within the hypothalamus during stress. At present, however, the possible pathophysiological relevance of the in vitro observations remains to be demonstrated.